P4_6 The Pot Noodle Proposal - Davis, Claire; Tilley, Freddie; Hague, Pete (Physics Special Topics, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-GB X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>It is claimed in the popular sitcom The Big Bang Theory that it is possible to heat up a pot of instant noodles with the laser that they have in a laboratory. This paper investigates the validity of the claim, and finds that although the laser can transfer enough energy for it to be possible, it would also destroy the container, thus rendering it pointless.